Arsenic speciation and transformation pathways in ground water system. - Rahul Kumar Chaudhary; Dr. Naveen Kumar Singh (The Bioscan, 2026)
Arsenic (atomic number, 33; relative atomic mass, 74.92) has chemical and physical properties intermediate between a metal and a non-metal, and is often referred to as a metalloid or semi-metal. It belongs to Group VA of the Periodic Table, and can exist in four oxidation states: –3, 0, +3, and +5. Arsenite, AsIII, and arsenate, AsV, are the predominant oxidation states under, respectively, reducing and oxygenated conditions (WHO, 2001; IARC, 2004). Arsenic is the 20th most common element in the earth’s crust, and is emitted to the environment as a result of volcanic activity and industrial activities. AsIII, MMAIII, and DMAIII can induce chromosomal aberrations in vitro (Oya-Ohta et al., 1996; Kligerman et al., 2003). Statistically significant increases in chromosomal aberrations occur only at toxic doses (Klein et al., 2007), except as a secondary effect of genomic instability in long-term, low-dose treatment protocols (Sciandrello et al., 2004). In the human body, inorganic arsenic compounds are converted to AsIII and AsV. AsV is rapidly converted to AsIII. AsIII species are more toxic and bioactive than are AsV species, both because of the greater chemical reactivity of AsIII, and because AsIII enters cells more easily. Many of these effects depend on altered gene expression that can result from genetic and epigenetic effects . Changes in gene expression by AsIII can also be mediated by the alteration of miRNA patterns (Marsit et al., 2006). Some short-term changes in gene expression (e.g. changes in the expression of DNA-repair proteins or DNA methyltransferases) can result in long-term changes. Genome-wide changes in gene expression and signal transduction induced by arsenicals have been reported in several publications (Su et al., 2006; Kumagai & Sumi, 2007; Ghosh et al., 2008). An analysis of micronuclei induced by AsIII in human fibroblasts shows that at lower (relatively non-toxic) doses, AsIII acts as an aneugen by interfering with spindle function and causing micronuclei with centromeres, but at high (toxic) doses, it acts as a clastogen, inducing micronuclei without centromeres (Yih & Lee, 1999). Aneuploidy is seen after treatment with AsIII concentrations lower than those that cause chromosomal aberrations (Yih & Lee, 1999; Ochi et al., 2004; Sciandrello et al., 2002, 2004).